2023
DOI: 10.1364/oe.495830
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of transverse mode instability by heat-load modulation

Abstract: We present the first experimental realization of a new mitigation strategy for TMI based on controlling the phase shift between the modal intensity pattern and the thermally induced refractive index grating. If specific modulation parameters are applied while pulsing the seed and/or pump radiation, the direction of energy transfer is forced from the higher-order modes into the fundamental mode. In this way, the fiber amplifier can operate at an average output power significantly higher than the TMI threshold w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…As a result, there is less heat accumulation, reducing the likelihood of thermal refractive index grating-induced TMI. Additionally, recent studies have shown that small-duty cycle pump modulation on the order of kHz can inhibit TMI 31 , 32 . Therefore, controlling SRS intensity is particularly important for high-power QCW fiber lasers and TMI is not considered in our simulation.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, there is less heat accumulation, reducing the likelihood of thermal refractive index grating-induced TMI. Additionally, recent studies have shown that small-duty cycle pump modulation on the order of kHz can inhibit TMI 31 , 32 . Therefore, controlling SRS intensity is particularly important for high-power QCW fiber lasers and TMI is not considered in our simulation.…”
Section: Resultsmentioning
confidence: 99%